Study on Rape and the Law in Karnataka: Exploring the Factors Influencing Rape Incidents and Conviction Rates in Karnataka (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Sexual offences against women, in different biological and psychological forms, have remained in practice, since thousands of years• back. However, in the contemporary period they are reported to be increasing every year. It is universally accepted that the root cause of this phenomenon inter-alia, lies in our social system, the historical position accorded to them, the religious myth, the roles modelled for them by the dominant section of the society. Any quest into the sexual offences. Particularly against women makes it imperative to trace back their position in the history, the roles which were exclusively modelled for them, the social status given to them in a particular period of time. The rape incident echoed in the assembly over the rape case of 6-year-old student in Bangalore’s private school recently on July 2, 2014. Blame game, instead taking collective responsibility by each elected member they just try to blame each other by the so-called elected representatives. Moreover, police have invoked Section 376 (rape) of IPC and Sections 4 and 6 of Prevention of Child Sexual Abuse (POCSO) Act 2012. Forget about the rape cases occurred at the remote places, today rapes have become very common in the school premises in a day light. Children are being easily targeted and victimizing, is it the effect of globalizing. In Karnataka over 1000 rapes have been reported in 2013 as per the State Crime Record Bureau. It means on an average around two rape cases have been registered in each day in 2013. The other pathetic condition in the state is that the rate of conviction in Karnataka was 11.6 per cent in 2010, dropping to 9.3 per cent in 2011. In 2012, just 434 of the 23,525 charge-sheeted, went to jail, forming 6.5 per cent (TOI Arun 30 Jan 2014).